Justice des mineurs, travail social et sexualité juvénile dans le Paris des années 1950 : une prise en charge genrée - Véronique Blanchard; Régis Revenin (Les Cahiers de Framespa)
This paper written by two persons wishes to compare the “reform school” treatment reserved to girls and boys in the fifties, and to measure the differences and similarities in this treatment. This is done using mostly professional reports and the own voices of these teenagers. The authors, working on similar sources, individual judicial files written from 1945 to the end of the fifties, emit the hypothesis that social and judicial norms imposed on the post-war youth were gender determinated. So, using several situations, it is shown that abnormality for the boys is related to homosexuality and prostitution, and sometimes with collective sexual violence against girls. For the girls, the problem is related to “normal” heterosexuality : sexual intercourse before marriage. Judicial sources demonstrate in an unusual way the customs and everyday life of the popular Parisian teenagers, mostly on the sexual matter.